Energy management system for a PV assisted conventional vehicle. (1st January 2013) - Sharma, Deepali; Gaur, Prerna; Mittal, A.P.
In this paper, a novel algorithm is proposed, for effective energy management of a conventional internal combustion engine vehicle, consisting of a photovoltaic (PV) source and battery also to power its electrical load. It offers a more practical and eco friendly solution of fossil fuel consumption reduction as compared to presently available alternatives such as electric/hybrid electric vehicles as it does not require construction of new infrastructure or replacement of current vehicle fleet. Effective control coordination among PV source, internal combustion (IC) engine connected rotating generator and battery is achieved during dynamical switching of the load between PV source, engine and battery. The DC bus voltage is maintained constant irrespective of variations in engine speed, PV power and load. Battery current control and maximum power point tracking of PV array is also carried out along with calculation of estimated fuel saving obtainable from the proposed system. Extensive MATLAB/Simulink simulations establish the satisfactory performance of the proposed energy management algorithm and controllers.